2005
DOI: 10.1038/sj.sc.3101844
|View full text |Cite
|
Sign up to set email alerts
|

Sexual rehabilitation of women with a spinal cord injury

Abstract: Results: The literature focuses on the effect of neurological change on women's ability to achieve sexual arousal and orgasm. Urinary and bowel incontinence, spasticity, vaginal lubrication and autonomic dysreflexia are the physical consequences of SCI that appear to have most impact on sexual activity. More recent studies have acknowledged that psychosocial factors such as age and partnership status may also affect the successful sexual rehabilitation. Discussions with women with SCI in Denmark and Sweden on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 38 publications
4
43
1
2
Order By: Relevance
“…17,[20][21][22][23] Our study further revealed that these concerns are severe enough to prevent a considerable number of women from seeking sexual activity with a partner. It is possible that the fear of incontinence may contribute to psychological aspects of arousal as well.…”
Section: Discussionmentioning
confidence: 62%
“…17,[20][21][22][23] Our study further revealed that these concerns are severe enough to prevent a considerable number of women from seeking sexual activity with a partner. It is possible that the fear of incontinence may contribute to psychological aspects of arousal as well.…”
Section: Discussionmentioning
confidence: 62%
“…9 Sexual function has also been recognized as an area that has not been sufficiently addressed 1 and most likely due to the sensitive nature of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Most women with SCI would have liked more sexual counseling during rehabilitation. 14 Our study has shown that 42.31% of patients preferred to receive this information while still at the hospital for rehabilitation. Many women also mentioned that the information was not given too soon after the injury, but that they should be informed about whom they could talk to when the need arose.…”
Section: Discussionmentioning
confidence: 99%